The Effect of Work Environment on Employee Performance at PT. Sinar Citra Abadi in Pamulang - Indra Novendri; Surya Budiman (Kontigensi : Jurnal Ilmiah Manajemen, 2021)
This study aims to determine the effect of the work environment on employee performance at P.T. Sinar Citra Abadi in Pamulang. The method used is explanatory research with a sample of 55 respondents. The analysis technique uses statistical analysis with regression, correlation, determination and hypothesis testing. This study of the work environment variable obtained an average score of 5.616 with suitable criteria. Employee performance variable obtained an average score of 5.729 with suitable criteria. The work environment has a positive and significant effect on employee performance with the regression equation Y = 20.320 + 0.658X, and the correlation coefficient value of 0.750 or has a strong relationship with a determination value of 56.3%. Hypothesis testing obtained a significance of 0.000 <0.05.